2016
DOI: 10.4172/2157-7560.1000331
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus Excretion among Persons with Primary Immune Deficiency Disorders: Summary of Data from Enhanced Poliovirus Surveillance in Egypt, 2011-2014

Abstract: Background: If exposed to oral poliovirus vaccine (OPV), persons with primary immune deficiency disorders (PID) are at increased risk of paralytic poliomyelitis; and can chronically excrete poliovirus. However, the risk of excretion of vaccine derived poliovirus among immunodeficient persons (iVDPV) is not well characterized. We present summary of data from poliovirus surveillance project among PID patients collected between 2011 and 2014 from 11 Egyptian Governorates. Methods: Stool was tested for polioviruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Most international reports associate iVDPV excretion with patients with antibody deficiency disorders [ 13 , 14 ]. SCID and combined immunodeficiencies are inherited predominantly in an autosomal recessive manner, thus in inbred populations, the collective results of the AFP surveillance confirmed that the majority of iVDPV cases were among combined immunodeficiency patients rather than among antibody deficiency disorders [ 15 , 16 ]. As SCID newborn screening is absent in Egypt, the discovery of most SCID patients is delayed after having received several OPV doses.…”
Section: Main Textmentioning
confidence: 86%
See 1 more Smart Citation
“…Most international reports associate iVDPV excretion with patients with antibody deficiency disorders [ 13 , 14 ]. SCID and combined immunodeficiencies are inherited predominantly in an autosomal recessive manner, thus in inbred populations, the collective results of the AFP surveillance confirmed that the majority of iVDPV cases were among combined immunodeficiency patients rather than among antibody deficiency disorders [ 15 , 16 ]. As SCID newborn screening is absent in Egypt, the discovery of most SCID patients is delayed after having received several OPV doses.…”
Section: Main Textmentioning
confidence: 86%
“…As reported by Driss et al [ 19 ] a Tunisian patient diagnosed with MHC II deficiency exhibited sequential infection by 9 different enterovirus serotypes within a 2-year period. El-Sayed et al [ 15 ] also reported on a PID patient who demonstrated evolution of VDPV in his stool samples over time which again highlights the importance of follow up as they may demonstrate intermittent shedding or evolution with time.…”
Section: Main Textmentioning
confidence: 98%
“…Although few cross-sectional studies have been conducted to identify iVDPV among PID patients without paralysis ( 12 , 17 21 ), this study identified the largest number of PID patients both with antibody and combined immune deficiencies. This study also constituted a large number of countries with worldwide distribution from four continents (Asia, Africa, Europe, and South America).…”
Section: Discussionmentioning
confidence: 98%
“…The striking concentration of iVDPV cases in the Middle East and North Africa may be due to: (1) an increased risk of PID due to co-sanguinity ( 29 ) and (2) an interest of immunologists in these Regions to strengthen surveillance for PID and create immunodeficiency registries. In particular, iVDPV surveillance projects have taken place in Egypt ( 30 ), Iran ( 31 ), and Tunisia ( 20 ).…”
Section: Discussionmentioning
confidence: 99%